The application and effectiveness of acceptance and commitment therapy on psychological resilience in the primary caregivers of ostomy patients - Li Teng; Xin Wu; Huili Xu; Yun Wang; Tian Luo; Adan Fu (Medicine, 2026)
Background: This study aims to investigate the effects of acceptance and commitment therapy (ACT) on enhancing psychological resilience, psychological flexibility, caregiving capacity, and benefit-finding among caregivers of ostomy patients. Methods: A total of 106 primary caregivers of ostomy patients were recruited from a tertiary hospital in Wuhan. Participants were randomly assigned to the intervention or control group in a 1:1 ratio using a computer-generated random sequence. Allocation was concealed using sequentially numbered, opaque, sealed envelopes prepared by a researcher not involved in recruitment or intervention delivery. The control group received standard nursing care, while the intervention group was provided with ACT in addition to standard care over a period of 12 weeks. The study utilized the 10-item Connor-Davidson Resilience Scale, Acceptance and Action Questionnaire-II (AAQ-II), Family Caregiving Task Inventory (FCTI), and Benefit Finding Scale to assess the outcomes before and after the intervention in both groups. Results: Post-intervention analysis showed that the intervention group had significantly lower AAQ-II scores and FCTI scores compared with the control group (AAQ-II: 19.57 ± 7.78 vs 24.04 ± 8.39; FCTI: 7.75 ± 3.69 vs 12.57 ± 6.76; P < .05), indicating improved psychological flexibility and caregiving ability. In contrast, the intervention group demonstrated significantly higher psychological resilience and benefit-finding scores compared with the control group (Connor-Davidson Resilience Scale: 24.94 ± 7.69 vs 20.89 ± 6.66; Benefit Finding Scale: 86.58 ± 7.47 vs 78.75 ± 8.12; P < .05). Conclusion: ACT was associated with improvements in psychological resilience, psychological flexibility, caregiving ability, and benefit finding among primary caregivers of ostomy patients. These findings suggest that ACT may be a useful supportive intervention for improving caregivers’ psychological adaptation and caregiving capacity.